The Effectiveness of Male-Targeted Sexual Assault Prevention Programs: A Meta-Analysis - Wright, Lauren A.; Zounlome, Nelson O. O.; Whiston, Susan C. (Trauma, violence & abuse, 2020)
According to Black et al., one in five women will be raped during their lifetimes. In one national survey, it was found that of 14,989 female college students from nine institutions, 34% reported experiencing a completed or attempted sexual assault in their lifetimes and 21% of them reported that they had experienced a completed or attempted sexual assault as a college student. Therefore, effective sexual assault prevention efforts targeted at men are needed, and several initiatives have been developed. The current study provides a meta-analytic investigation of male-targeted sexual assault prevention interventions. Eligible studies were located from the following databases: Psychological Information Database, Education Resources Information Center, Medical Literature Analysis and Retrieval System Online, Google Scholar, Dissertation Abstracts Online, Criminal Justice Abstracts, and reference sections of relevant articles. The weighted mean effect size for between-subjects studies of sexual assault attitudes showed improvement (d = −0.24, k = 25), and the effect was statistically significant (p < .001). The weighted mean effect size for between-subjects studies of future inclinations toward engaging in sexually aggressive behavior (d = −0.20, k = 13, p = .02) and toward engaging in sexual assault prevention behavior (d = 0.27, k = 10, p = .007) showed statistically significant improvements as well. However, the weighted mean effect sizes for between-subjects studies of rape empathy, sexual assault knowledge, sexual assault–related attitudes, and sexual assault perpetration were nonsignificant. Results show there is significant room for growth, both in terms of practical applications and further research.